Analisis Buku Teks Al-Arabiyyah Linnasyiin 2 Berdasarkan Kriteria Rusydi Ahmad Thu'aimah - Budianto, Firman; Nikmatullah Husni; Moh. Aman (INTIFA: Journal of Education and Language, 2025)
ABSTRACT This research aims to determine how the publishing and design, linguistic content and teaching, cultural content and teaching, exercises and evaluation and companion of the Arabic language textbook Al-Arabiyyah Linnasyiin 2 are based on Rusydi Ahmad Thuaimah's criteria. This research was conducted using a qualitative method with the type of library research, data collection methods by means of documentation, and data analysis methods by means of reducing data, presenting data, drawing conclusions, and verifying. The conclusions obtained from this research indicate that the publishing and design of this book are in accordance with Rusydi Ahmad Thuaimah's criteria, except for some basic elements of book preparation. The linguistic content and teaching of this book is in accordance with the criteria, except for some elements of teaching letters and sounds, dealing with differences between students, and elements of grammatical terminology. The cultural content and teaching of this book is in accordance with the criteria, except for the elements of the different cultural content frameworks and the elements of the author's orientation towards culture. The exercises and evaluation of this book are in accordance with the criteria, except for the elements of phonetic exercises and all elements of tests and evaluations. The companion book in this book is in accordance with the criteria for the type of teacher's guide only. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana penerbitan dan rancangannya, konten linguistik dan pengajarannya, konten budaya dan pengajarannya, latihan dan evaluasinya dan pendamping buku teks bahasa Arab Al-Arabiyyah Linnasyiin 2 berdasarkan kriteria Rusydi Ahmad Thuaimah. Penelitian ini dilakukan dengan metode kualitatif dengan jenis penelitian kepustakaan (library research), metode pengumpulan data dengan cara dokumentasi, dan metode analisis data dengan cara mereduksi data, menyajikan data, menarik simpulan, dan melakukan verifikasi. Kesimpulan yang diperoleh dari penelitian ini menunjukkan bahwa penerbitan dan rancangan buku ini sesuai dengan kriteria Rusydi Ahmad Thuaimah, kecuali untuk beberapa unsur dasar-dasar penyiapan buku. Konten linguistik dan pengajaran buku ini sesuai dengan kriteria, kecuali untuk beberapa unsur pengajaran huruf dan bunyi, menghadapi perbedaan antara siswa, dan unsur terminologi tata bahasa. Konten budaya dan pengajaran buku ini sesuai dengan kriteria, kecuali untuk unsur kerangka konten budaya yang berbeda-beda dan unsur orientasi penulis terhadap budaya. Latihan dan penilaian buku ini sesuai dengan kriteria, kecuali untuk unsur latihan fonetik dan semua unsur tes dan penilaian. Pendamping buku pada buku ini sesuai kriteria pada jenis panduan guru saja.